21st Century: Art in the first decade - Claire Bishop; Ian McLean; Nancy Adjania; Terry Smith; TJ Demos; Wallace, Miranda (South Brisbane; Queensland Art Gallery, 2011)
Exhibition catalog. Dec 2010-Apr 2011 @Queensland Art Gallery. Texts: Kathryn Weir, Russell Storer, Nicholas Chambers, Jose Da Silva, David Burnett, Julie Ewingotn, Kobena Mercer,Terry Smith, Ian McLean, Nancy Adjania, TJ Demos, Claire Bishop, Juliana Engberg, Manuel J Borja-Villel, Rex Butler.
English
Keywords: 21st century; Contemporary Art; N4390-5098 Exhibitions